Detection of circulating immunosuppressive cytokines in malignant pleural mesothelioma patients for prognostic stratification. (October 2021) - Urso, Loredana; Silic-Benussi, Micol; Boscolo, Alice; Lorenzi, Martina; Bonanno, Laura; Lunardi, Francesca; Guarneri, Valentina; Calabrese, Fiorella; Rea, Federico; Conte, PierFranco; Pasello, Giulia
Highlights: No prognostic circulating biomarker is available in MPM. High monocytes count showed a negative prognostic value. High levels of monocytes, IL10, TGF-β showed association with shorter OS and PFS. Chemotherapy induced an increase in monocytes, IL-10, but not TGF-β levels. Abstract: Background: No data on circulating biomarkers for the prognostic stratification of Malignant Pleural Mesothelioma (MPM) patients are available. We prospectively explored the prognostic role of circulating monocyte and cytokine levels and their dynamic change during chemotherapy. Patients and Methods: MPM patients receiving a first line treatment based on a platinum compound plus pemetrexed were eligible. Blood samples were collected at the baseline and at the end of induction chemotherapy. CCL-2, IL-10 and TGF-β levels in plasma were quantified by Enzyme-Linked Immunosorbent Assay (ELISA); white blood cells, monocytes and platelets were evaluated by blood count test. Results: Thirty-one patients were included in the study. Median overall survival (OS) was 12.13 months versus 9.6 months in patients with lower and higher monocytes count, respectively (p value = 0.02). We further stratified patients according to a combined score based on the association of IL-10, TGF-β levels and monocytes count. High combined score was associated with shorter OS and PFS in univariate and multivariate analysis. Chemotherapy induced an increase in monocytes, IL-10, but not TGF-β levels. Conclusion: The prognostic value of circulating levels of multiple immunosuppressive cytokines and inflammatory cells should be confirmed in a wider validation set of MPM patients.